Suffix Study ια - Philip Suciadi Chia; Juanda Juanda (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2020)
The use of the suffix ια is interesting to study. According to Buck and Petersen combined words in -ια, Ion. -ιη, and those in -ιӑ in the same list because of practical convenience and their interrelations in Greek. On the other side there are uses that actually have their own peculiarities. There are many substantives without connections with adjectives in -ιος because prehistoric substantivations may be surmised. Καρδίας (in genitive) is an example of old concrete substantives in -ια is related to Hittie gen. kardias. Words in -ιă or -įāreflect a type which in the other IE languages appears as an ī/yā stem such as in Sankrit (nom. devī, acc. devīm, gen. devyās, dat.devyāi, etc.).